সেই সে কাল : সরদার ফজলুল করিম - ফজলুল করিম, সরদার, ১৯২৫-; University of Dhaka. Institute of Modern languages (ঢাকা : প্যাপিরাস, 2002)
Autobiographical reminiscences of a leftist leader, university teacher, and writer from Bangladesh about his involvement in political activities before the independence of his country in 1971.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Fazlul Karim, Sardar, -- 1925- -- Political activity; Political activists -- Bangladesh -- Biography; Communists -- Bangladesh -- Biography; Bangladesh -- Politics and government